2021
DOI: 10.3390/f12121712
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization, Pathogenicity and Biological Characterization of Colletotrichum Species Associated with Anthracnose of Camellia yuhsienensis Hu in China

Abstract: Camellia yuhsienensis Hu, a species of tea oil tree with resistance to anthracnose, is widely used to breed disease-resistant Camellia varieties. In 2019, anthracnose symptoms were observed on Ca. yuhsienensis for the first time. However, the species and biological characteristics of Colletotrichum spp. isolated from Ca. yuhsienensis (YX-Colletotrichum spp.) have not been elucidated. In this study, five isolates (YX2-5-2, 2YX-3-1, 2YX-5-1, 2YX-8-1-1 and 2YX-8-1-2), which were consistent with the morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…A previous report showed that C. fructicola is a non-host-specific pathogen infecting fruit, vegetables, and economic crops, including apple (Malus pumila) [37], sugarcane (Saccharum officinarum) [38], blueberry (Vaccinium corymbosum) [53], and Camellia yuhsienensis [54]. C. fructicola was described as a common species existing on the leaves of tea-oil camellia [35].…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that C. fructicola is a non-host-specific pathogen infecting fruit, vegetables, and economic crops, including apple (Malus pumila) [37], sugarcane (Saccharum officinarum) [38], blueberry (Vaccinium corymbosum) [53], and Camellia yuhsienensis [54]. C. fructicola was described as a common species existing on the leaves of tea-oil camellia [35].…”
Section: Discussionmentioning
confidence: 99%
“…Colonies on WA with sterilized sticks, reaching 5 cm diam after 7 d at room temperature (±25 • C), under light 12 h/dark 12 h, colonies rhizoid to filamentous, dense, flat surface, with filiform margin, dark green from above and reverse, with producing pycnidia on sticks and immersed pycnidia under media. Hosts and Distribution: Actinidia chinensis, China [56], Japan [57]; Aesculus chinensis, China [58]; Amomum villosum, China [59]; Anacardium occidentale, Brazil [60,61]; Annona spp., Brazil [62,63]; Anthurium, Sri Lanka [64]; Arachis hypogaea, China [65]; Areca catechu, China [66,67]; Atractylodes ovata, Korea [68]; Aucuba japonica, China [69], Korea [70]; Averrhoa carambola, China [71]; Bletilla striata, China [72]; Brassica spp., China [73]; Camellia chrysantha, China [74]; Camellia grijsii, China [75,76]; Camellia oleifera, China [77]; Camellia sinensis, China [67,[78][79][80][81][82][83], Indonesia [42,80]; Capsicum spp., China [84,85], Thailand [86]; Carica papaya, Mexico [87]; Carya spp., China [88][89][90][91]; Cattleya spp., Brazil [92]; Ceanothus thyrsiflorus, Italy…”
Section: Colletotrichum Fructicola Prihast L Cai and Kd Hyde Fungal D...mentioning
confidence: 99%
“…C. oleifera has large fruits with rich oil content but is sensitive to anthracnose ( Wang et al., 2017 ; Li et al., 2021 ; Quan et al., 2022 ). Camellia yuhsienensis Hu, a relative of C. oleifera in the genus Camellia , is characterized by high oil quality and strong resistance to anthracnose, a source of natural resistance for use in elite cultivars ( Chen et al., 2021 ; Li et al., 2021 ). Crossbreeding is a crucial part of the C. oleifera tree breeding program because of its self-incompatibility ( Liao et al., 2014 ; Goulet et al., 2017 ; Lenzi et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%